Regulation of Legal Protection for Notaries in Performing Official Duties to Ensure Legal Certainty and Justice - Agnes Nova Randomis (Pusat Publikasi Nusantara, 2025)
Notaries as public officials who are authorized to make authentic deeds have an important position in the Indonesian legal system. However, in practice, notaries often face legal problems that arise due to the implementation of their duties, both in the criminal, civil, and professional ethical realms. This paper aims to analyze the regulation of legal protection for the duties of the notary position and provide ideas for normative reconstruction to be in line with the principles of legal certainty and justice. The research method used is a normative approach with analysis of laws and regulations, legal doctrine, and case studies. The results of the study show that the regulation of legal protection for notaries in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Notary Position is still partial and has not provided comprehensive protection. Policy reconstruction is needed through strengthening legal protection norms that include aspects of office responsibility, fair supervision mechanisms, and limits on the intervention of law enforcement officials. Thus, legal protection for notaries will further ensure legal certainty and justice for the parties and the community.